Clarification of magnetic levitation force and stability property of multi-seeded YBCO in point of supercurrent coupling effect - Ozturk, K.; Kabaer, M.; Abdioglu, M.; Patel, A.; Cansiz, A. (Elsevier BV, 2016)
Abstract In our study as different from the literature, which are mostly related to superconductor fabrication, application and optimization, especially physical origins of bulk supercurrent generation, magnetic levitation and stability properties of the multi-seeded YBCO superconductor are investigated in point of supercurrent coupling effect. Besides the experimental measurements, a simplified simulation of the supercurrent coupling in the multi-seeded bulk YBCO is carried out based on the experimental J c (B) data taken from literature and using the critical state method and H-formulation together in COMSOL Multiphysics package, to further elucidate the mechanism of supercurrent generation and guidance force. The bigger guidance force and lateral magnetic stiffness values of PMG-B arrangement with three B z peaks than the other arrangements with one B z peak in small cooling height of 5 mm are attributed to the more robust individual intragrain supercurrents, rather than intergrain supercurrent, due to the position coincidence in the z-direction between grains and permanent magnet poles. Additionally, it can be said that PMG-C arrangement with one B z peak getting to the maximum guidance force value when the cooling height increase from 5 mm to 15 mm, points out for large cooling height the intergrain supercurrents dominate, whereas for the small cooling height the intragrain supercurrents have most effect on the guidance force. Also, performed the supercurrent simulations, using different current flow constraint ratio f (or supercurrent coupling parameter), clearly reproduced the qualitative change in the trapped field profile when the allowed intergrain current compared to no intergrain current (f = 0). It is thought that the presented results, related to the supercurrent generation, coupling mechanism and their effect on levitation and lateral force properties, have utilization potential for researches not only they study on new multiseed superconductor fabrication method, but also they study on superconductor applications.
Keywords: Yttrium barium copper oxides; Multi-seeded YBCO; Permanent magnets; Magnetic devices; Magnetism; Levitation force; Superconducting materials; Critical current density (superconductivity); Magnetic energy densities; Supercurrent coupling; Permanent magnet poles; Permanent magnet; Magnetic levitation; Magnets; Magnetic levitation vehicles; Magnetic energy density; Magnetic levitation force; Supercurrents; Cooling; Stability; YBCO superconductor; Stability properties